Heat Engineering Justification on Selection of Energy Efficient Refractory Lining of Reheating and Heat-Treating Furnaces at Machine Manufacturing Enterprises - V. I. Timoshpolsky; L. A. Trusova; A. P. Nesenchuk; D. V. Mendelev; M. L. German (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An algorithm for selection of an energy efficient refractory lining has been developed on the basis of a ratio of summed-up capital expenditure and operating costs.A non-linear problem of thermal conductivity in a layer of the fiber refractory lining has been numerically solved in the paper. The paper determines an actuality of the fiber refractory lining application at the temperature level of 55–75 °C  (on the average65 °C) on its external surface.A mathematical solution of a refractory layer selection has been executed in the paper. The paper gives several variants of the arrangement  of three-layer fiber refractory lining.